2006
DOI: 10.1002/polb.20867
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated poly(aryl ether ether ketone ketone)s containing fluorinated moieties as proton exchange membrane materials

Abstract: A series of sulfonated poly(aryl ether ether ketone ketone)s statistical copolymers with high molecular weights were synthesized via an aromatic nucleophilic substitution polymerization. The sulfonation content (SC), defined as the number of sulfonic acid groups contained in an average repeat unit, could be controlled by the feed ratios of monomers. Flexible and strong membranes in sodium sulfonate form could be prepared by the solution casting method, and readily transformed to their proton forms by treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
2
23
0
2
Order By: Relevance
“…Our earlier work has shown that pendent phenyl rings attached to electron-donating polymer chain sites can be preferentially sulfonated at the para position, without obvious chain degradation occurring during sulfonation. [39][40][41][42][43] In the present study, the copolymers 2-PAES-60 and 4-PAES-20, having pendent phenyl groups on the electron-withdrawing site of the polymer chain were sulfonated on the para-phenyl position with chlorosulfonic acid to produce PS2-PAES-60 and PS4-PAES-20, respectively ("postsulfonation" is distinguished by PS). On the basis of experimental IEC w values, a 5-fold molar excess of chlorosulfonic acid was necessary for complete sulfonation.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier work has shown that pendent phenyl rings attached to electron-donating polymer chain sites can be preferentially sulfonated at the para position, without obvious chain degradation occurring during sulfonation. [39][40][41][42][43] In the present study, the copolymers 2-PAES-60 and 4-PAES-20, having pendent phenyl groups on the electron-withdrawing site of the polymer chain were sulfonated on the para-phenyl position with chlorosulfonic acid to produce PS2-PAES-60 and PS4-PAES-20, respectively ("postsulfonation" is distinguished by PS). On the basis of experimental IEC w values, a 5-fold molar excess of chlorosulfonic acid was necessary for complete sulfonation.…”
Section: Methodsmentioning
confidence: 99%
“…SPAEEKK based membranes still dissolved into the Fenton reagent in about 1 h because of its high degree of sulfonation [32]. However, the oxidation of hydrocarbon-based membranes in Fenton reagent is not necessarily indicative or a good predictor of their durability under fuel cell operation, since sulfonated poly(ether ether ketone) membranes have shown lifetimes over 1000 h in either PEMFC and DMFC tests [55,56].…”
Section: Proton Conductivity Of the Membranesmentioning
confidence: 99%
“…The fluorinated moieties in sulfonated poly(arylene ether ether ketone ketone) (SPAEEKK) increase the hydrophobicity of polymer and enhance the formation of separated hydrophobic and hydrophilic domains in its microstructure, thereby providing the proton conducting domains [32]. Addition of silica to SPAEEKK membranes through the sol-gel process formed hybrid membranes, which showed decreased methanol crossover.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonated poly(aryl ether ether ketone ketone)s (SPEEKKxx, where xx = 40, 50, 60, 70, 80, and 100 with DS = 0.8, 1.0, 1.2, 1.4, 1.6, and 2.0) were prepared by Liu et al (34). The structures of the polymer containing the 6F or 6FP groups are shown in Scheme 1 (1-1).…”
Section: Sulfonated Fluorinated Random Copoly(arylene Ether)smentioning
confidence: 99%